Point prevalence survey on antibiotic use in the hospitals of Mauritius - Veerapa-Mangroo, Lovena Preeyadarshini; Rasamoelina-Andriamanivo, Harena; Issack, Mohammad Iqbal; Cardinale, Eric (Frontiers in Antibiotics, 2023)
Background: This study aims at determining the antibiotic prescribing pattern in admitted patients in the regional public hospitals of Mauritius. Methods: A Point Prevalence Survey (PPS) on antibiotic use according to the World Health Organization Methodology for PPS on antibiotic use in hospitals, was carried out in 3 secondary public hospitals. Data was collected in February 2018 for Hospital 1 and in April-May 2019 for Hospital 2 and Hospital 3. Eligible inpatients were those who were hospitalized in the ward at 8.00 a.m. on the day of the survey. Results: Among 915 inpatients, 482 (53%) were treated with 753 therapies or prescriptions of antibiotics, averaging 1.6 therapies or prescriptions per patient. Among those treated with antibiotics, an average of 88 patients (55%), 58 patients (36%) and 15 patients (9%) were given 1, 2 and 3 or more antibiotics respectively. The highest proportion of inpatients treated with antibiotics was among those with community acquired infections (n=243, 50%) followed by surgical prophylaxis (n=191, 40%). In the three hospitals, it was observed that third generation cephalosporins (ceftriaxone, cefotaxime), amoxicillin, metronidazole (parenteral) and ciprofloxacin accounted for more than 75% of total prescriptions and sixteen per cent (16%) of patients had an Antibiotic Susceptibility Testing report before prescription of antibiotics. Conclusion: This study provides valuable information on antibiotic use in the country. Several misuses have been identified such as the excessive use of antibiotics for surgical prophylaxis, the high use of third generation cephalosporins and of the WATCH category of antibiotics. It also demonstrates a low percentage of Antibiotic Susceptibility Testing prior to prescription of antibiotics. This investigation shows that there is now a pressing need to repeat the Point Prevalence Survey on antibiotic use in hospitals in future whilst extending the survey to the private healthcare system to get a complete picture concerning antibiotic use in Mauritius.